2021
DOI: 10.13057/asianjagric/g050103
|View full text |Cite
|
Sign up to set email alerts
|

Grape supply chain: Vertical coordination in Ningxia, China

Abstract: Abstract. Li S, Bitsch L, Hanf JH. 2021. Grape supply chain: Vertical coordination in Ningxia, China. Asian J Agric 5: 12-21. Since 2018, China has been the second-largest grape-growing country in the world, with 875 thousand hectares in total. A former study indicated a transformation within the wine grape supply chain management in the Chinese wine market, from traditional coordination to significant vertical integration. The Ningxia Helan Mountain’s Eastern Foothill wine region (China) is considered to be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 0 publications
4
13
0
Order By: Relevance
“…play essential roles in the decisions of supply chain management and contractual relationship. For emerging wine regions some results confirm earlier findings of other studies such as firm size, product quality and the level of specialised investments matter for coordination decisions (Bitsch et al, 2019;Chaddad et al, 2017;Hanf et al, 2016;Li et al, 2021). Goodhue et al (2003) find that more formal coordination is associated with higher product quality.…”
Section: Value Chain Coordination In the Global Agribusiness And Wine...supporting
confidence: 85%
“…play essential roles in the decisions of supply chain management and contractual relationship. For emerging wine regions some results confirm earlier findings of other studies such as firm size, product quality and the level of specialised investments matter for coordination decisions (Bitsch et al, 2019;Chaddad et al, 2017;Hanf et al, 2016;Li et al, 2021). Goodhue et al (2003) find that more formal coordination is associated with higher product quality.…”
Section: Value Chain Coordination In the Global Agribusiness And Wine...supporting
confidence: 85%
“…In line with the findings of Li et al (2021), Changyu procures grapes in different manners. On the one hand, it uses spot market transactions; on the other hand, it procures grapes from the integrated cooperative (vertically integrated).…”
Section: Structure Of Changyu-led Cooperative and Coordination Mechan...supporting
confidence: 79%
“…As the local government in Ningxia also promotes the production of high-quality wines (Wang et al, 2012), the production concept applied by Changyu is assumed to differ in both regions. Li et al (2021) examined the structure and mechanisms of grape supply models and degree of vertical coordination in Ningxia (Ningxia Helan Mountain's Eastern Foothill wine region). They have shown that most wine producers apply "multi-supply models".…”
Section: Jadee 132mentioning
confidence: 99%
See 2 more Smart Citations